2016
DOI: 10.1890/15-1152.1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced facilitation at the extreme end of the aridity gradient in the Atacama Desert: a community‐level approach

Abstract: Plant facilitation is now recognized as an important process in severe environments. However, there is still no agreement on how facilitation changes as conditions become increasingly severe. The classic stress gradient hypothesis (SGH) predicts a monotonic increase in facilitation, which rises in frequency as conditions approach the extreme end of the environmental gradient. However, few studies have evaluated the validity of the SGH at the community level, the level at which it was formulated. Moreover, few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Low WHC may be representative of a resource‐conservative strategy as we find it in stressful environments (Wright et al., ). It has been suggested that facilitation is particularly important in such environments (López, Squeo, Armas, Kelt, & Gutiérrez, ; Maestre, Callaway, Valladares, & Lortie, ). The observed synergy in decomposition might be another form of facilitation, which has not been recognized so far: synergistic decomposition might indeed increase nutrient availability and benefit to both species providing the mixed litter.…”
Section: Discussionmentioning
confidence: 99%
“…Low WHC may be representative of a resource‐conservative strategy as we find it in stressful environments (Wright et al., ). It has been suggested that facilitation is particularly important in such environments (López, Squeo, Armas, Kelt, & Gutiérrez, ; Maestre, Callaway, Valladares, & Lortie, ). The observed synergy in decomposition might be another form of facilitation, which has not been recognized so far: synergistic decomposition might indeed increase nutrient availability and benefit to both species providing the mixed litter.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by a variety of ecologists (Butterfield 2009, Armas et al 2011, He et al 2013, Michalet et al 2014, Soliveres et al 2015, Liancourt et al 2017, the apparently opposing views of the original and recent versions of the SGH may stem from inter-study differences in the nature of stress gradients (resource or non-resource stress), life-history of response species (stress tolerant or competitively inferior), scale of study focus (community or species level), component of stress factors (single or multiple stresses), or whether the observed gradient is complete. Even though a large number of studies from various ecosystems have explored the SGH, empirical tests of the hypothesis in extreme environments remains insufficient (but see Armas et al 2011, de Bello et al 2011, Castanho et al 2015, Lopez et al 2016, Liancourt et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…) may alter the frequency and strength of facilitation among plants (Malkinson and Jeltsch , López et al. ). This is important because we have observed (1) size‐specific differences in drought tolerance, for Ambrosia in particular (Miriti et al.…”
Section: Resultsmentioning
confidence: 99%